Management skills in a construction consultancy: a qualitative analysis - Fernández Gónzales, Jessica (2021)
Addressing the issue of Management Skills today is of great relevance since it is part of the backbone of any organization. The objective of this research with a qualitative approach, with a phenomenological design, was to analyze the management skills in a construction consulting company in Lima in 2020, for which interviews were applied to five collaborators including the manager of the organization. In addition, a free software version Atlas ti 8 was used for the analysis and interpretation of the data. In the results, the a priori category managerial skills was established with its three subcategories (human, technical and conceptual) and two emerging categories: adaptation to change and the ability to delegate. It was concluded that management skills are inefficient or are not adequately developed from the perspective of employees, as well as affirming that they are not satisfied with the performance of their manager.